Digital Learning Innovation Through Learning Management System (LMS) for Paket C at PKBM: Preliminary Research - Syahri, Achmad; Rejekiningsih, Triana; Santosa, Eka Budhi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
This research aims to identify various needs from the point of view of pro-spective students studying package C (Paket C) regarding a technology-based learning platform in the Learning Management System (LMS) format. This research is a preliminary that uses a quantitative descriptive design approach. The research sample consisted of 35 people who included students or resi-dents studying package C. Data collection techniques used questionnaires and were analyzed on a percentage basis. The findings in this research indi-cate that students have a positive view of the presence of LMS to facilitate their learning. According to him, the presence of the LMS will be able to make learning more flexible in terms of time, they can still work and be ac-tive but on the other hand they can also continue to attend lessons whose material they can access at the LMS. In the context of learning package C, this research has the potential to provide a strong basis for the development of further learning innovations. By utilizing LMS technology, related parties can design learning approaches that are more effective, inclusive, and re-sponsive to students' needs and learning styles. It is hoped that through this research it can become the basis for the development of a learning innova-tion for package C learning residents.